Usability evaluation checklist for smartphone app - Rahmat, Hazwani; Zulzalil, Hazura; Ghani, Abdul Azim Abd.; Kamaruddin, Azrina (Medwell Journals, 2017)
This study proposed a model for usability evaluation in view of smartphone characteristic, user interface design and context of use approach. A set of mobile related bibliographic has been reviewed. In addition, 3 usability features, 11 usability criteria and 33 UI elements have been identified. Finally, a set of 84 checklist items has resulted and paired to the identified UI elements. In this research, it has been found that nteraction and notification are the main emphasis aspect of app usability. This has been supported by the large distribution of the checklist on usability criteria such as promptness, ease of use and interactivity which govern by the highlighted usability features. The UI elements distribution also conformsto these results. It is shown that besides text, UI element such as dialogue, button and navigation drawer has been the main building blocks in designing an App. While previous studies evaluate appbased on either by traditional computing design elements, ergonomics or HCI perspectives this study address usability of App by incorporating measurement from previous studies in user interface elements of App adopted in the industry while at the same time, acknowledging the different set of evaluator skill.